2022
DOI: 10.3390/ijerph19020964
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Treatment with Neuromuscular Functional Electrostimulation of Antagonistic Muscles and Kinesiotherapy Evaluated with Electromyography and Clinical Studies in a Two-Month Follow-Up

Abstract: The aim of this study was to determine the sustained influence of personalized neuromuscular functional electrical stimulation (NMFES) combined with kinesiotherapy (mainly, proprioceptive neuromuscular facilitation (PNF)) on the activity of muscle motor units acting antagonistically at the wrist and the ankle in a large population of post-stroke patients. Clinical evaluations of spasticity (Ashworth scale), manual muscle testing (Lovett scale), and surface electromyography recordings at rest (rEMG) and during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Herein, we retrospectively analyzed the clinical data of femoral neck fracture patients with severe stroke hemiplegia admitted to the Guangdong Hospital of Traditional Chinese Medicine in Guangzhou, China, between January 2015 and December 2020, with a minimum 1-year follow-up. The inclusion criteria were: femoral neck fracture and stroke hemiplegia, unilateral lower extremity muscular strength < grade 3/5 (Lovett scale) ( 15 ), and treatment at our institution. The exclusion criteria included bilateral lower extremity impairment, revision arthroplasty, pathological fractures, less than one year of follow-up, and lack of specific information.…”
Section: Methodsmentioning
confidence: 99%
“…Herein, we retrospectively analyzed the clinical data of femoral neck fracture patients with severe stroke hemiplegia admitted to the Guangdong Hospital of Traditional Chinese Medicine in Guangzhou, China, between January 2015 and December 2020, with a minimum 1-year follow-up. The inclusion criteria were: femoral neck fracture and stroke hemiplegia, unilateral lower extremity muscular strength < grade 3/5 (Lovett scale) ( 15 ), and treatment at our institution. The exclusion criteria included bilateral lower extremity impairment, revision arthroplasty, pathological fractures, less than one year of follow-up, and lack of specific information.…”
Section: Methodsmentioning
confidence: 99%
“…Physical examination showed that the myodynamia of the distal muscle strength of the right lower limb was level 3, and the distal muscle strength of the right lower limb was level 1 by Lovett's scale. 8,9 The patient had a previous history of old cerebral infarction for 6 years, old myocardial infarction for 4 years, but did not have hypertension nor diabetes mellitus.…”
Section: Case Reportmentioning
confidence: 99%
“…An urgent issue of modern kinesiology is the search for effective ways of using the results of scientific research in biomechanics and physiology to counter the processes of disadaptation. The problem of studying the mechanisms of restoring the capabilities of body systems after a long period of disadaptation caused by various factors is a priority task for a number of scientists [7][8][9]. The main issue for determining the periodization and spectrum of methods to use for the neuromuscular system readaptation is to conduct a detailed analysis of the functional and physical state of a person after a period of disadaptation.…”
Section: Introductionmentioning
confidence: 99%
“…In the available literature, there are various directions of using exercises in kinesiotherapy to solve problems with the musculoskeletal system [3,4,7,11]. However, practicing only various exercises with standard load parameters may not always correspond to the body resistance level and contribute to readaptation processes.…”
Section: Introductionmentioning
confidence: 99%